PEMBERANTASAN KORUPSI PERSPEKTIF HUKUM PIDANA ISLAM - Romziatussa’adah, Romziatussa’adah (Universitas Islam Negeri Raden Fatah Palembang, 2014)
Abstract: Corruption in Indonesia is actually a phenomenon of ironic because the people known as the religious community but its remains rampant behavior developed. Behavior destructive impact of corruption on society. The increasing rate of poverty due to the limited employment opportunities, mainly due to corruption of government officials do. Facts speak that corruption in Indonesia has reached the limit of severe and entrenched. Rational effort-conducted systematic government to eliminate a step that must be supported together. In Islamic criminal law of corruption the same as al-ghulul, al-risywah and al-ghasab. Forms of crime greater sin than theft, but the smaller legal sanctions. This is due to the orthodox Islamic jurists hold that the penalty for jarimah not exceed ta'zir on jarimah hudud criminal-Qisas..ملخص: الفساد في اندونيسيا هو في الواقع ظاهرة السخرية ، لأن الشعب يعرف المجتمع الدينية ولكن يظل الفساد المستشري السلوك المتقدمة. السلوك الأثر المدمر للفساد على المجتمع. ازدياد معدل الفقر بسبب محدودية فرص العمل ، ويرجع ذلك أساسا إلى الفساد من مسؤولي الحكومة القيام به. الحقائق تتحدث بأن الفساد في اندونيسيا قد وصلت الى حد شديد وراسخة. جهود الرشيد ، أجرت الحكومة منهجية للقضاء على الخطوة التي يجب دعمها معا. في القانون الجنائي الإسلامي للفساد في نفس القاعدة. أشكال الجريمة أكبر خطيئة من السرقة، ولكن أصغر العقوبات القانونية. هذا يرجع إلى الفقهاء المسلمين الارثوذكس ان عقد لعقوبة التعزيرجريمه يجب ألا تتجاوز العقوبة على جريمه الحدية - القصاص.Kata Kunci: korupsi, hukum pidana islam.